Development and Validation of a Circumplex Measure of the Interpersonal Culture in Work Teams and Organizations - Locke, Kenneth D. (Frontiers in Psychology, 2019)
Interpersonal circumplex inventories assess a range of dispositions but can condense and compare their findings within a circular model defined by two factors: agency and communion. Whereas other interpersonal circumplex inventories assess individuals, the current research introduces IPC inventories assessing the interpersonal culture (interaction and communication norms) characterizing an entire organization or team—namely, the Circumplex Culture Scan (CCS) and Circumplex Team Scan (CTS). Across an initial development sample (n = 1676), online validation sample (CCS n = 808; CTS n = 832), and onsite validation sample (CCS n = 516 respondents from 21 organizations; CTS n = 347 respondents from 38 teams), the eight 8-item CCS/CTS octant scales demonstrated good internal consistencies, circumplex properties, reliable within-group agreement and between-group variance (thus justifying aggregation across an organization/team), and convergent, discriminant, and incremental validity in relation to other measures. According to their members, the organizations/teams with the most satisfied members and customer/clients were organizations/teams with considerably stronger communal (e.g., being open, respectful) than uncommunal (e.g., being rude, guarded) norms and somewhat stronger agentic (e.g., being eager, assertive) than unagentic (e.g., being cautious, quiet) norms. The CCS/CTS complements existing IPC and organizational culture measures and helps bridge the interpersonal circumplex and organizational literatures.